ENVIRONMENTALLY FRIENDLY BRIQUETTES MADE FROM A MIXTURE OF SNAKE FRUIT SKIN AND GOAT MANURE - Rotami, Ladya; Wardana, Rendy Wikrama; Setiawan, Iwan; Anjarsari, Putri; Firdaus, M. Lutfi (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2025)
The purpose of this study is to make snake fruit briquette charcoal mixed with goat dung an alternative energy source that supports environmentally friendly technology. The samples used were snake fruit and goat dung as charcoal and tapioca flour as an adhesive. Each sample has 200 grams of charcoal and 30 grams of adhesive. The percentage of charcoal is 50% snake fruit bark charcoal and 50% goat dung charcoal. Snake fruit briquettes and goat dung are divided into 3 groups: A1 (87% charcoal: 13% adhesive), A2 (77% charcoal: 23% adhesive), and A3 (97% charcoal: 3% adhesive). In 3 samples tested with the percentage of charcoal flour to tapioca flour, the first one was produced in sample A1 (87%: 13%), which produced a moisture content of 9.87%, an ash content of 36.75%, and a calorific content of 5899 kcal/kg. The A2 sample (77%:23%) yielded a moisture content of 11.44%, an ash content of 32.13%, and a calorific content of 5634 kcal/kg. The A3 sample yielded a moisture content of 8.93%, an ash content of 41.38%, and a calorific content of 6339 kcal/kg.  This study concludes that the best calorific value in the A3 sample is 97% charcoal briquettes with 3% adhesive, with a calorific value of 6339 cal/kg.